Cervical Cancer Screening Program by Visual Inspection: Acceptability and Feasibility in Health Insurance Companies - Apollinaire G. Horo; Judith Didi-Kouko Coulibaly; Abdoul Koffi; Boris Tchounga; Konan Seni; Kacou Edèle Aka; Mamourou Kone (Obstetrics and Gynecology International)
Objective. To assess willingness to participate and diagnostic accuracy of visual inspection for early detection of cervical neoplasia among women in a health insurance company. Patients and Method. Cervical cancer screening was systematically proposed to 800 women after consecutive information and awareness sessions. The screening method was visual inspection with acetic acid (VIA) or Lugol’s iodine (VILI). Results. Among the 800 identified women, 640 (82%) have accepted the screening, their mean age was 39 years, and 12.0% of them were involved in a polygamist couple. 28.2% of women had prior cervical screening. VIA has been detected positive in 5.9% of women versus 8.6% for VILI. The sensitivity was 72.9% and specificity was 95.2% for VIA versus 71.2% and 97.3% for VILI respectively. The histological examination highlighted a nonspecific chronic cervicitis in 4.6%, CIN1 lesions in 5.91%, and CIN2/3 in 1.2% of the cases. Conclusion. Cervical cancer screening by visual inspection showed appropriate diagnostic accuracy when used to detect early cervical lesions. It is a simple and easy to perform method that could be introduced progressively in the health insurance policy while waiting for a national screening program.